Narrowing the interface between sample preparation and electrochemistry: Trace-level determination of emerging pollutant in water samples after in situ microextraction and electroanalysis using a new cell configuration - Gabbana, Jéssica Vita; de Oliveira, Luiz Henrique; Paveglio, Guilherme Caneppele; Trindade, Magno Aparecido Gonçalves [UNESP] (Elsevier, 2018)
In this work, a new cell configuration that enables the in situ integration of sample preparation and electrochemical detection prior analysis at trace-level is described. To perform the microextraction, a green chemistry extractor solvent, so called deep eutectic solvent (DES) was used, which allowed the pre-concentration of ciprofloxacin (CIPRO) from water samples. The particular characteristics of the featured device include: reduction of the number of steps involved in conventional liquid-liquid microextraction, processing the pre-concentration of target analyte in a small drop that can be directly decanted onto the electrode surface and further electroanalysis at a single time in order to achieve the required trace-level quantity. After the optimization of parameters inherent to the system, with the aid of chemometric approach, the proposed device enabled fast electroanalysis of CIPRO at concentration levels down to 5.00 nmol L−1 with suitable accuracy, since the recovery values were ranged between 71 and 93%.
Keywords: Contaminant of emerging concern; Electroanalysis at trace-level; In situ microextraction; Residual drugs determination